Michael, Thomas (coord.) (2010): Diercke International Atlas - Soriano, Joan Manuel (Documents d'Anàlisi Geogràfica, 2011)
Michael, Thomas (coord.) (2010) Diercke International Atlas Brunswick (Alemanya): Westermann, 227 p. ISBN: 978-3-14-100790-9